Algoritmo para ajuste automático de ganho em tempo real para circuito flexível de condicionamento de sinal - Texeira, Tiago Augusto (2019)
The growing need for more effective control in electrical power systems (generation, trans mission and distribution) has made the development of smart grids (SG) the main object of study for many researchers. In this context and looking for the integration and convergence of different systems to construct a SG infrastructure is proposed and implemented an algorithm to control parameters associated with a circuit for flexible signal conditioning applied to an intelligent electronic device in SG applications. Then, based on this signal conditioning circuit, a flexible intelligent electronic device (DEIF) was developed. This device differs from other intelligent electronic devices IEDs as it performs the different signals acquisition (voltage, current, temperature, pressure, etc.) with different conditioning values (e.g. gain and offset), in addition with the possibility of performing self-conditioning by software. The flexible intelligent electronic device can operate, among other applicati ons, as a two-way smart meter, as a dynamic (local) controller and/or as a supervisory controller, thereby improving system efficiency, reliability and safety. Other advantages of the proposed solution are: low cost, versatility (changes can be made by software), high processing capacity (uses an ARM processor), communication capabilities (hybrid architecture network), easy integration, interoperability, easy maintenance, modularity and scalability. A DEIF prototype is presented and its effectiveness, flexibility and versatility are experimentally demonstrated.